3xy+5=ax-7

Simple and best practice solution for 3xy+5=ax-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3xy+5=ax-7 equation:


Simplifying
3xy + 5 = ax + -7

Reorder the terms:
5 + 3xy = ax + -7

Reorder the terms:
5 + 3xy = -7 + ax

Solving
5 + 3xy = -7 + ax

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1ax' to each side of the equation.
5 + -1ax + 3xy = -7 + ax + -1ax

Combine like terms: ax + -1ax = 0
5 + -1ax + 3xy = -7 + 0
5 + -1ax + 3xy = -7

Add '-5' to each side of the equation.
5 + -1ax + -5 + 3xy = -7 + -5

Reorder the terms:
5 + -5 + -1ax + 3xy = -7 + -5

Combine like terms: 5 + -5 = 0
0 + -1ax + 3xy = -7 + -5
-1ax + 3xy = -7 + -5

Combine like terms: -7 + -5 = -12
-1ax + 3xy = -12

Reorder the terms:
12 + -1ax + 3xy = -12 + 12

Combine like terms: -12 + 12 = 0
12 + -1ax + 3xy = 0

The solution to this equation could not be determined.

See similar equations:

| 10+0.5m=23.5 | | 592+76(21[18*4]+48)7*88= | | 7+4xy+3+xy= | | n-1=11-n | | 33*26-33*22=33*(-22) | | 4(t+p)-3=6+-13 | | .25x+.5=.5 | | 5=14v-9v | | 2(k-3)=3(k-4) | | 101=x+3x+(x+4) | | -3x-1=-37 | | 45m=120 | | 8x(x+2)=0 | | 10x-2x-15=27+3x | | 4(w+9)=20 | | 12g^2+16g-3=0 | | 6+m=21 | | 9v^2-55v+50=0 | | a=bcW+x-y | | 11-3-2x+3x=4x-4 | | 7x-58=2x-8 | | (5x)-6-7x=2 | | 6x+(x-16)=180 | | 10+50m=110 | | 0.33+2=6x-73 | | -55.2=6.9c | | 4(4x+6)=2(8x+12) | | 2(6c+8)=4+6c | | 26=b-16 | | 3t^2-9t=12 | | 50+10m=110 | | V=(3.14)(2*2)(150) |

Equations solver categories